2013
DOI: 10.3758/s13421-013-0339-0
|View full text |Cite
|
Sign up to set email alerts
|

Reducing reliance on inaccurate information

Abstract: People learn from the texts that they read, but sometimes what they read is wrong. Previous research has demonstrated that individuals encode even obvious inaccuracies, at times relying on the misinformation to complete postreading tasks. In the present study, we investigated whether the influence of inaccurate information might be reduced by encouraging the retrieval of accurate knowledge. Participants read an extended text that contained both accurate and inaccurate assertions, after which they evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 56 publications
2
70
0
Order By: Relevance
“…Apparently, validation processes can be prevented by a very low standard of coherence that forgoes the need for semantic processing. Validation processes might even be goal-dependent as suggested by studies showing that readers' sensitivity to false or implausible information seems to vary with their goals (e.g., Rapp, Hinze, Kohlhepp, & Ryskin, 2014) and are dependent on text characteristics, most notably text genre. For example, narratives seem to invoke an immersed state of processing (transportation, Gerrig, 1993) that makes readers particularly susceptible to false or implausible information (e.g., Appel & Richter, 2007).…”
Section: Validation and Standards Of Coherencementioning
confidence: 99%
“…Apparently, validation processes can be prevented by a very low standard of coherence that forgoes the need for semantic processing. Validation processes might even be goal-dependent as suggested by studies showing that readers' sensitivity to false or implausible information seems to vary with their goals (e.g., Rapp, Hinze, Kohlhepp, & Ryskin, 2014) and are dependent on text characteristics, most notably text genre. For example, narratives seem to invoke an immersed state of processing (transportation, Gerrig, 1993) that makes readers particularly susceptible to false or implausible information (e.g., Appel & Richter, 2007).…”
Section: Validation and Standards Of Coherencementioning
confidence: 99%
“…research has demonstrated that, when readers come across misinformation in a text that clearly contradicts prior knowledge, they will later answer general knowledge questions based on the misinformation they recently read rather than their accurate prior knowledge (Eslick, Fazio, & Marsh, 2011;Fazio, Barbar, Rajaram, Ornstein, & Marsh, 2013;Hinze, Slaten, Horton, Jenkins, & Rapp, 2014;Marsh & Fazio, 2007;Rapp, Hinze, Kohlhepp, & Ryskin, 2014). Thus, when source information is not available within texts, readers appear to apply problematic strategies to resolve coherence breaks, without actually re-establishing global coherence of what was read (Stadtler & Bromme, 2014;Chinn & Brewer, 1998).…”
Section: Characterizing Source Processing and Representation: Introdumentioning
confidence: 99%
“…In addition to these declarative kinds of statements, evidence for reliance on inaccurate information has also been obtained with stories containing more general assertions about the world. These assertions represent cases in which the accumulated evidence from personal experience and outside sources should suggest one particular view or claim is likely to be valid, even though alternative hypotheses might be considered but necessarily discarded as wrong (Appel & Richter, ; Gerrig & Prentice, ; Prentice et al, ; Rapp, Hinze, Kohlhepp, & Ryskin, ). After reading incorrect assertions such as “Tides are not controlled by the moon's gravitational pull” or “Tooth brushing increases the likelihood of gum disease,” participants have more difficulty subsequently judging the truth underlying those ideas than after reading accurate versions of such assertions (e.g., “Tides are controlled by the moon's gravitational pull” or “Tooth brushing reduces the likelihood of gum disease.”) Norming studies for the facts and assertions used in these projects indicate that the ideas underlying these topics should be well known to participants (Nelson & Narens, ; Rapp et al, ; Tauber, Dunlosky, Rawson, Rhodes, & Sitzman, ).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these processing tendencies could offer explanations as to the influence of inaccurate information described in previous work. Some recent accounts have indeed contended that these routine processes of memory and comprehension can result in products that exemplify a reliance on inaccurate information (Marsh, Cantor, & Brashier, ; Rapp & Donovan, ; Rapp et al, ).…”
Section: Introductionmentioning
confidence: 99%